Development of new sol-gel derived Ag-doped biomaterials for dental applications - Chatzistavrou, Xanthippi; Kontonasaki, Eleana; Bakopoulou, Athina; Theocharidou, Anna; Sivropoulou, Afroditi; Paraskevopoulos, Konstantinos M.; Koidis, Petros; Boccaccini, Aldo R.; Kasuga, Toshihiro (Materials Research Society, 2012)
The aim of this work was to develop a new Ag-doped bioactive material with antibacterial behavior, optimizing the properties of the new fabricated composite material in the system SiO 58.6 -PO 7.2 -AlO 4.2 -CaO 24.9 -NaO 2.1 -KO 3 (wt%). Two systems with different concentrations in Ag O (Ba with 2.1 and Bb with 4.2 wt%) were prepared by the sol-gel method and compared to the respective silver-free control composite (CONTROL). The microstructural characteristics of the developed compositions were characterized by different techniques as UV/VIS spectroscopy, X-ray diffraction analysis (XRD) and Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS). The antibacterial properties of the Ag-doped glass-ceramics were tested against the bacterial colony Staphylococcus aureus (S. aureus) which is very characteristic oral bacteria and the material-cell interaction was monitored in a primary culture of Human Gingival Fibroblasts (HGFs). Our study shows the successful incorporation of the silver ions in the ceramic structure and the preparation of new Ag-doped composite materials with cell-proliferation-inductive, as well as antibacterial properties indicating their potential application dental tissue restoration strategies. © 2012 Materials Research Society.